OWE-20 Survival & fungal catheter related blood stream infections in patients on HPN. (June 2019) - Oke, SM; Miah, N; Fourali, N; Khanna, P; Donnelly, SC; Small, M; Gabe, SM
Abstract : Introduction: Candidiasis is associated with significant morbidity & mortality. Central venous catheters (CVC) are commonly used for home parenteral nutrition (HPN) in patients with intestinal failure (IF) & are commonly linked to development of candidaemia. We aim to describe the long-term survival in patients with candidal catheter related blood stream infections (CRBSI) in the IF population & assess factors that may be associated with poorer outcome. Methods: Clinical records of patients receiving HPN at our unit were reviewed between 1/1/2007 to 1/5/2018. Candidal CRBSI was defined as either: documented or reported positive cultures from the CVC line with negative peripheral cultures, peripheral cultures with time to positivity faster than CVC cultures, paired positive cultures from CVC & peripheral blood with symptoms of sepsis, or positive CVC tip culture following CVC removal. Demographic data, underlying aetiology, small intestinal length, colonic continuity, long-term survival & cause of death were recorded. Data were also collated on number of candidal CRBSI, candidal species, bacterial co-infection, antifungal resistance together with opiate & immunosuppression use at the time of infection. Differences between groups were analysed using Chi-Squared tests, Kaplan-Meier & Cox's regression model were used to assess factors affecting survival. Results: 66 patients were identified of whom 22 (33.3%) were male. The mean age was 49.4 (SD 16.5). 13 (19.7%) patients had multiple candidal CRBSI. Candida galbrata & albicans accounted for 32 (48.5%) of the index infections. 8 (12%) patients had candidal species that were resistant to ≥1 anti-fungal agent. 48 (72.7%) patients were receiving an opiate at the time of the fungal CRBSI, & 8 (12.1%) were receiving some form of immunosuppression. 25 (38%) patients died during the study period. The 1, 5 & 10 year survival rates were 97%, 67% & 53% respectively. From the time of first fungal CRBSI, the 1, 5 & 10 year survival rates were 85%, 55% & 27%. No difference was seen in survival between patients who had single & multiple candidal infections (log-rank p=0.669). On multivariate analysis increasing age (HR 1.08 p=0.02), increasing time of HPN prior to index infection (HR 0.45 p<0.005), length of residual small intestinal length (HR 0.76 p=0.06) underlying aetiology (HR 6.40 p=0.017) & opiate use (HR 39.5 p=0.003) were all associated with long-term survival. Conclusion: Our data have shown long-term survival after index fungal CRBSI in the IF population are poor. A better prognosis is associated with a small intestinal length of ≥ 150cm & increasing length of time on HPN prior to first infection. A worse prognosis is associated with underlying aetiology including mesenteric infarction & scleroderma & the use of opiates.